Characterization of Batracylin-induced Renal and Bladder Toxicity in Rats. (June 2015) - Davis, Myrtle; Bunin, Deborah I.; Samuelsson, Steven J.; Altera, Kenneth P.; Kinders, Robert J.; Lawrence, Scott M.; Ji, Jiuping; Ames, Matthew M.; Buhrow, Sarah A.; Walden, Chad; Reid, Joel M.; Rausch, Linda L.; et al.
Batracylin (NSC-320846) is a dual inhibitor of DNA topoisomerases I and II. Batracylin advanced as an anticancer agent to Phase I clinical trials where dose limiting hemorrhagic cystitis (bladder inflammation and bleeding) was observed. To further investigate batracylin's mechanism of toxicity, studies were conducted in Fischer 344 rats. Once daily oral administration of 16 or 32 mg/kg batracylin to rats for 4 days caused overt toxicity. Abnormal clinical observations and adverse effects on clinical pathology, urinalysis, and histology indicated acute renal damage and urothelial damage and bone marrow dysfunction. Scanning electron microscopy revealed sloughing of the superficial and intermediate urothelial layers. DNA damage was evident in kidney and bone marrow as indicated by histone γ-H2AX immunofluorescence. After a single oral administration of 16 or 32 mg/kg, the majority of batracylin was converted to N-acetylbatracylin (NAB) with a half-life of 4 hr to 11 hr. Mesna (Mesnex™), a drug known to reduce the incidence of hemorrhagic cystitis induced by ifosfamide or cyclophosphamide, was administered to rats prior to batracylin, but did not alleviate batracylin-induced bladder and renal toxicity. These findings suggest that batracylin results in DNA damage-based mechanisms of toxicity and not an acrolein-based mechanism of toxicity as occurs after ifosfamide or cyclophosphamide administration.